Analysis and improved process response prediction of laser- assisted automated tape placement with PA-6/carbon tapes using Design of Experiments and numerical simulations. (May 2017) - Schaefer, P.M.; Gierszewski, D.; Kollmannsberger, A.; Zaremba, S.; Drechsler, K.
Abstract: Laser-assisted thermoplastic automated tape placement (LATP) enables the additive manufacturing of composites. The quality of parts depends on the temperature distribution during processing and on the thermal history of the laminate. We demonstrate that process response variables e.g., maximum process temperature and the thermal history can be predicted by surrogate models. These models are analytical models, which are created by a Design of Experiments approach. They are evaluated in real time and allow for the fast prediction of process responses as a function of different process parameters. The models are based on data, which are obtained by computer experiments with a 2D simulation model of the LATP process. The surrogate models were applied to analyze the effects of process parameter variations. The laser power and placement velocity were found to be most influential. The capability to make these process predictions in real-time presumably improves manufacturing of complex shaped parts.